The humanistic tradition - Fiero, Gloria K. (McGraw Hill, 2006)
Contents: Prehistory to the modern world; The early modern world to the present; The European Renaissance, the Reformation and global encounter; Faith, reason, and power in the early modern world; Romanticism, realism, and the nineteenth-century world; Modernism, globalism, and the information age.